Identity : The Demand for Dignity and the Politics of Resentment - Fukuyama, Francis (New York Picador, 2019)
"The New York Times bestselling author of The Origins of Political Order offers a provocative examination of modern identity politics: its origins, its effects, and what it means for domestic and international affairs of state. In 2014, Francis Fukuyama wrote that American institutions were in decay, as the state was progressively captured by powerful interest groups. Two years later, his predictions were borne out
Include Notes, Bibliography and Index
Keywords: Identity politics -- World politics